A window of opportunity for cooperativity in the T Cell Receptor - N. Martin-Blanco (Nature Portfolio, 2018)
T cells can be activated by a small, two-digit, number of antigen peptide molecules even though the receptor for antigen (TCR) is of low affinity. Here the authors present evidence that all TCRs within a nanocluster can become activated when only a subset is bound to antigen.